The Human Resource Management at The Directorate General of Taxes (Ministry of Finance) to Increase Indonesia's Tax Ratio - Desiyanto, Arif (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
The tax-to-GDP ratio is the ratio of the tax revenue of a country compared to the country's gross domestic product (GDP). This ratio isused as a measure of how well the government controls a country's economic resources. Tax-to-GDP ratio is calculated by dividing the taxrevenue of a specific time period by the GDP. (https://www.investopedia.com/terms/t/tax-to-gdp-ratio.asp). Indonesia's tax-to-GDPratio was 10.1% in 2020, below the Asia and Pacific (28) average of 19.1% by 9.0 percentage points. It was also below the OECDaverage (33.5%) by 23.4 percentage points. The tax-to-GDP ratio in Indonesia decreased by 1.5 percentage points from 11.6% in 2019to 10.1% in 2020. From 2007 to 2020, the tax-to-GDP ratio in Indonesia decreased by 2.1 percentage points from 12.2% to 10.1%.The highest tax-to-GDP ratio in this period was 13.0% in 2008, and the lowest 10.1% in 2020. The author tries to find the cause ofthe low tax ratio in Indonesia from the point of view of human resources, in this case, the tax officials. The author tries to examine therelationship between the number of tax officials and the number of taxpayers who must be supervised. In addition, the author will alsoexamine the management of human resources at the Directorate General of Taxes in an effort to increase Indonesia's tax ratio. TheDirectorate General of Taxes (DGT) intends to raise the present tax ratio to 15%, aligns with the global average. Indonesia’s current taxratio of 10.4% is still below the global average of 13.5%, as per the DGT. Indonesia is also trailing behind other nations in the ASEANregion; for instance, Thailand’s tax ratio is at 14.5%, the Philippines at 14%, and Singapore at 12.9%.(https://indonesiabusinesspost.com/, DGT efforts to increase Indonesia’s tax ratio up to 15%)Keywords: tax ratio, human resources management, tax official